Modeling of Wound Rotor Synchronous Machines considering Harmonics, Geometric Saliencies and Saturation induced Saliencies - Rambetius, Alexander; Luthardt, Sven; Piepenbreier, Bernhard (International Power Electronics Conference - ECCE Asia, 2014)
Advanced control techniques for wound rotor synchronous machines need precise machine models. Often a simple fundamental wave model is used to design the control algorithms. Using such a model, it is not possible to account for non-ideal effects that distort the control algorithm. Therefore a general machine model is derived by extending classical winding function theory. This analytical machine model considers higher harmonics as well as geometric saliencies and saturation induced secondary saliencies and leads to new insights for wound rotor synchronous machines. Firstly it is shown that, under certain conditions, the stator slots induce higher harmonics in the rotor winding. Moreover cross saturation effects are described. Last but not least the machine model provides information about the origin of certain harmonics and about their phase depending on saturation. The suggested machine model is verified experimentally by measurement results. © 2014 IEEE.
UnivIS-Import:2015-04-16:Pub.2014.tech.IE.LEEAS.modeli
Keywords: EESM; harmonics; saturation; synchronous motor; winding function theory; wound rotor synchronous machine